Asset pricing models: evidence from the Indian equity market. (4th November 2022) - Choudhary, Kapil; Kumar, Parveen; Mehta, Sakshi
The asset pricing model has been a core area of research in finance due to its applicability in corporate finance and security analysis. The present study attempted to evaluate the three popular asset pricing models viz., the capital asset pricing model, the Fama-French three-factor model, and the Fama-French five-factor model in the Indian equity market for the period of January 2009 to November 2018. The study also examined the role of the size, profitability, value, investment, and market factors in explaining the average equity returns in the Indian equity market. The empirical results reveal the inferior performance of a single market factor in describing the variations in average stock returns in comparison with the Fama-French three-factor model and the Fama-French five-factor model. Further, the size and value factors added to CAPM yield a vital melioration in explaining the variation in average returns of sample stocks.